Re-conociendo la cerámica del sitio arqueológico La Ponga, provincia de Santa Elena, Ecuador - Pablo Quelal Madrid (Bulletin de l'Institut Français d'Études Andines)
This article provides the results of a study of the ceramics of La Ponga, collected by Pedro Porras in 1976-1977. It includes an analysis of attributes and their organization into a typology, followed by a seriation of the types formed. The elements identified are used to produce a definition of the Machalilla culture. In addition, with the support of an evaluation of the archaeological investigations of the south-central coast of Ecuador, the observation of attributes and ceramic types makes it possible to propose a variant located in the indicated area, which is distinguished from the ceramics of the classic Machalilla site. This pottery style is close in time to the Chorrera-Engoroy culture.